Several problems in survey of buildings finished with face brick in Saint-Petersburg - V.M. Ogorodnik; Y.V. Ogorodnik (Инженерно-строительный журнал, 2010)
The authors emphasize two types of brick walls defects: defects of mortar and defects of masonry stones. Causes of these defects are analysed, such as moisturing of masonry; material quality; quality of contractor work; project errors.